System approach for flood vulnerability and community resilience assessment at the local level – a case study of Sakon Nakhon Province, Thailand - Pal, Indrajit; Doydee, Puvadol; Utarasakul, Tatsanawalai; Jaikaew, Piyanuch; Azahari Bin Razak, Khamarrul; Fernandez, Glenn; Huang, Tailin; Siau Chen, Chian (Kasetsart Journal of Social Sciences, 2021)
Field-based academic researches play a vital role in the identification of key issues contributing to disaster vulnerability and in uncovering of policy recommendations that will help in reducing vulnerability and improving community resilience. Vulnerability to disasters is embedded in a complex system of societal structures and processes. It is driven by a combination of social, economic, environmental, institutional, and other relevant processes that interact with and influence each other. Thus, assessment of disaster vulnerability requires an approach that captures the dynamics of drivers of disaster vulnerability and accounts for the interactions among them. System approach to disaster vulnerability assessment could be an effective method to understand the drivers of disaster vulnerability and interactions among them. The system approach seeks to look at a problem in its entirety, considering all the facets, all the intertwined parameters to identify the optimum solutions to the problem. Thus, the primary objective of this paper is to review the existing field-based approaches to flood vulnerability assessment aimed at understanding the extent to which system approach has been adopted and identifying gaps in current approaches. Along with a comprehensive review of existing researches on flood vulnerability assessment, this paper will also use learnings from an on-going research project on flood vulnerability assessment using system approach at the local level in Sakon Nakhon Province, Thailand.